Comparative Analysis of LCX and Bidirectional Antenna Performance in Jakarta MRT Telecommunication System - INDRA FIRMANSYAH KOSWARA; ROBBY KURNIAWAN HARAHAP (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Telecommunication system reliability is critical to the operation of the Jakarta MRT, particularly for Train-to-Ground communication, CCTV transmission, and passenger information services. This study compares the performance of Leaky Coaxial Cable (LCX) and bidirectional antennas using MATLAB-based numerical simulation founded on a modified empirical propagation model, evaluated at frequencies of 5.2 GHz and 5.8 GHz over distances of 10–2000 m, with path loss, SNR, BER, and effective throughput as the analyzed parameters. At a distance of 2000 m and a frequency of 5.2 GHz, LCX yielded a path loss of 149.2255 dB, an SNR of -14.2586 dB, a BER of 0.3921, and a throughput of 6.0792 Mbps, outperforming the bidirectional antenna, which yielded a path loss of 156.8298 dB, an SNR of -21.8629 dB, a BER of 0.4546, and a throughput of 5.4543 Mbps.